2007
DOI: 10.1021/pr070203n
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Proteomic Profiling of the Normal Human Kidney Glomerulus Using Two-Dimensional Protein Prefractionation in Combination with Liquid Chromatography-Tandem Mass Spectrometry

Abstract: The kidney glomerulus plays a pivotal role in ultrafiltration of plasma into urine and also is the locus of kidney disease progressing to chronic renal failure. We have focused proteomic analysis on the glomerulus that is most proximal to the disease locus. In the present study, we aimed to provide a confident, in-depth profiling of the glomerulus proteome. The glomeruli were highly purified from the kidney cortex from a male, 68-year-old patient who underwent nephroureterectomy due to ureter carcinoma. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 24 publications
2
52
1
Order By: Relevance
“…Only proteins identified in at least two of three biologic replicate analyses were included in the dataset, and identified ECM proteins were further categorized as basement membrane proteins (Table 1), other structural ECM proteins (Table 2), or ECM-associated proteins (Supplemental Table 2). There are a number of published glomerular proteomic studies, [21][22][23][24][25] and a comparison was made with protein identifications in our dataset ( Figure 3). Of two published studies for which complete MS datasets were available, 22,25 neither study enriched for glomerular ECM or analyzed more than one biologic replicate.…”
Section: Defining the Glomerular Ecm Proteomementioning
confidence: 99%
“…Only proteins identified in at least two of three biologic replicate analyses were included in the dataset, and identified ECM proteins were further categorized as basement membrane proteins (Table 1), other structural ECM proteins (Table 2), or ECM-associated proteins (Supplemental Table 2). There are a number of published glomerular proteomic studies, [21][22][23][24][25] and a comparison was made with protein identifications in our dataset ( Figure 3). Of two published studies for which complete MS datasets were available, 22,25 neither study enriched for glomerular ECM or analyzed more than one biologic replicate.…”
Section: Defining the Glomerular Ecm Proteomementioning
confidence: 99%
“…17, 18 We performed a comprehensive proteomic analysis of this subfraction enriched in GMVs (apical membrane vesicles) and then assessed the overlap of our GMV proteome with the published glomerular tissue and urine exosome proteomes. 19 We studied the post-translational processing of a number of known glomerular disease proteins for the first time in vivo and provide these data in a searchable database.…”
mentioning
confidence: 99%
“…Control of the P1 and P2 promoters would influence the expression of MB- and S-COMT isozymes. In fact, proteome analyses of kidney indicated that COMT is expressed in the glomerulus [23,24]. Oxidative stress was shown to inhibit the activity of S-COMT [25].…”
Section: Discussionmentioning
confidence: 99%